Crowding in public transport: Who cares and why?. (June 2017) - Haywood, Luke; Koning, Martin; Monchambert, Guillaume
Abstract: Crowding on public transport (PT) is a major issue for commuters around the world. Nevertheless, economists have rarely investigated the causes of crowding discomfort. Furthermore, most evidence on the costs of PT crowding is based on trade-offs between crowding, travel time and money. First, this paper assesses discomfort with PT crowding at various density levels across heterogeneous individuals using a different methodology. Based on a survey of 1000 Paris PT users, the negative relationship of in-vehicle density on reported satisfaction is similar to previous studies investigating PT crowding costs and stable across most individual characteristics. We also find a sensitive increase in crowding costs over users' income. Second, we investigate the causes of this discomfort effect. We identify three key drivers: (a) dissatisfaction with standing and not being seated; (b) less opportunities to make use of the time during the journey; (c) the physical closeness of other travelers per se .